2019
DOI: 10.1038/s41467-019-12999-5
|View full text |Cite
|
Sign up to set email alerts
|

A combination of chitooligosaccharide and lipochitooligosaccharide recognition promotes arbuscular mycorrhizal associations in Medicago truncatula

Abstract: Plants associate with beneficial arbuscular mycorrhizal fungi facilitating nutrient acquisition. Arbuscular mycorrhizal fungi produce chitooligosaccharides (COs) and lipo-chitooligosaccharides (LCOs), that promote symbiosis signalling with resultant oscillations in nuclear-associated calcium. The activation of symbiosis signalling must be balanced with activation of immunity signalling, which in fungal interactions is promoted by COs resulting from the chitinaceous fungal cell wall. Here we demonstrate that CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
183
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 161 publications
(221 citation statements)
references
References 78 publications
17
183
0
Order By: Relevance
“…Probably, it is from the differences in nature of the signaling triggered by mixture and a particular CTOS as seen in previous studies and discussed by Bi and Zhou (61) and by Yamaguchi et al (62). Studies have shown that interactions between different oligosaccharides play important roles in determining signaling specificity (63). An interesting possibility is that CSOS in the crude chitin preparation may interact with CTOS to define CTOS signaling specificity.…”
Section: Ctos As a Model Fungal Mamp To Study Fungus-induced Stomatalmentioning
confidence: 99%
“…Probably, it is from the differences in nature of the signaling triggered by mixture and a particular CTOS as seen in previous studies and discussed by Bi and Zhou (61) and by Yamaguchi et al (62). Studies have shown that interactions between different oligosaccharides play important roles in determining signaling specificity (63). An interesting possibility is that CSOS in the crude chitin preparation may interact with CTOS to define CTOS signaling specificity.…”
Section: Ctos As a Model Fungal Mamp To Study Fungus-induced Stomatalmentioning
confidence: 99%
“…Thus, it is possible that the two species interact in the wild, but it is unlikely that the specific temperate genotype of R. irregularis isolate we obtained co-evolved with M. truncatula populations. We note however, that temperate isolates of R irregularis have previously been used to study plant mycorrhizal interactions in M. truncatula (Kiirika et al, 2012;Afkhami and Stinchcombe, 2016;Feng et al, 2019). For those pots receiving AM fungi, pots were first filled with 300 mL of sterile soil, and then the remaining 300 mL of soil was mixed with 1.5 g of inoculum powder (800 spores/g), and this mixture was then added to the pot.…”
mentioning
confidence: 99%
“…The above-described chitin, Myc factors and Nod factors, β-glucans and peptidoglycan are the most well-characterized microbial cell wall polysaccharides that act as IPs. Besides these, more cell wall components are recognized by plants, such as fungal COs, cyclic β-glucans (Pettolino et al, 2009;Feng et al, 2019) and bacterial lipopolysaccharides (LPS) (Wang and Quinn, 2010;Erbs and Newman, 2012), and probably many more remain to be discovered. Therefore, microbial cell walls can be considered a rich source of IPs, some of which are not only perceived by plants, but also by human and animal immune systems (Ariizumi et al, 2000;Kumar et al, 2009;Bozza et al, 2009;Brown, 2011;Rosadini and Kagan, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Besides chitin, plant LysM-containing receptors play essential roles in perceiving chitin derivatives such as lipochitooligosaccharides (LCOs), molecules with a chitin backbone that generally consists of four or five residues and an acyl chain attached to the non-reducing terminal GlcNAc that are known to act as Nod factors, rhizobial signal molecules that are essential for the initiation of a symbiosis with legume plants (Gough, 2003;Gust et al, 2012). Similarly, arbuscular mycorrhizal (AM) fungi secrete LCOs that are known as Myc factors in combination with chitooligosaccharides (COs) to initiate their symbiosis (Gust et al, 2012;Liang et al, 2014;Limpens et al, 2015;Feng et al, 2019). The perception of Nod or Myc factors in various plant species involves receptor complexes with LysM-RLKs (Gough, 2003;Maillet et al, 2011;Genre et al, 2013;Liang et al, 2014;Zipfel and Oldroyd, 2017).…”
Section: Lysm Receptors Mediate Mutualistic Symbiosesmentioning
confidence: 99%
See 1 more Smart Citation